CDX2: A Prognostic Marker in Metastatic Colorectal Cancer Defining a Better BRAF Mutated and a Worse KRAS Mutated Subgroup - Aasebø, Kristine; Dragomir, Anca; Sundström, Magnus; Mezheyeuski, Artur; Edqvist, Per-Henrik; Eide, Geir Egil; Ponten, Fredrik; Pfeiffer, Per; Glimelius, Bengt; Sorbye, Halfdan (Frontiers in Oncology, 2020)
Background: Survival of metastatic colorectal cancer (mCRC) patients has improved, but mainly for trial patients. New predictive and prognostic biomarkers validated in the general mCRC population are needed. Caudal-type homeobox 2 (CDX2) is an intestine-specific transcription factor with potential prognostic and predictive effect, but the importance in mCRC has not been fully investigated. Methods: Immunohistochemistry analysis of CDX2 was performed in a Scandinavian population-based cohort of mCRC (n=796). Frequency, clinical and tumour characteristics, response rate, progression-free survival (PFS) and overall survival (OS) were estimated. Results: Loss of CDX2 expression was found in 87 (19%) of 452 stained cases, in 53% if BRAF mutated (BRAFmut) and in 9% if KRAS mutated (KRASmut). CDX2 loss was associated with microsatellite instability, BRAFmut, poor differentiation and inversely associated with KRASmut. Patients with CDX2 loss received less 1st-line (53% vs. 64%, p = 0.050) and 2nd-line (23% vs. 39%, p = 0.006) chemotherapy and secondary surgery (1% vs. 9%, p = 0.019). Median PFS and OS for patients given 1st-line combination chemotherapy was 4 and 10 months if CDX2 loss vs. 9 and 24 months if CDX2 expressed (p = 0.001, p < 0.001). Immediate progression on 1st-line combination chemotherapy was seen in 35% of patients with CDX2 loss vs. 10% if CDX2 expressed (p = 0.003). Median OS in patients with BRAFmut or KRASmut and CDX2 expressed in tumour (both 21 months) was comparable to wildtype patients (27 months). However, if CDX2 loss, median OS was only 8 and 11 months in BRAFmut and KRASmut cases, respectively, and 10 months in double-wildtype patients. In multivariate analysis, CDX2 loss (hazard ratio (HR): 1.50, p = 0.027) and BRAFmut (HR: 1.62, p = 0.012) were independent poor prognostic markers for OS. Conclusion: In a population-based cohort of mCRC patients, CDX2 loss is an independent poor prognostic marker. Expression of CDX2 defines a new subgroup of BRAFmut cases with a much better prognosis. Loss of CDX2 defines a small group of KRASmut cases with a worse prognosis. Patients with CDX2 loss receive less palliative chemotherapy with less benefit and rarely reach secondary surgery.